On the relativistic nature of predicted and real physical experiences: A field experiment - Slawinska, M.; Papaioannou, A.; Chatzisarantis, Nikos; Hatzigeorgiadis, A.; Davis, P. (Elsevier Ltd, 2015)
Objectives: An important yet unresolved question stemming from judgment and decision-making literature is whether individuals evaluate physical experiences in relative or absolute terms. Design and method: The study examined 181 experienced basketball players in a 2 (type of experience: predicted versus real)×2 (evaluation mode: separate versus joint)×2 (type of activity: running versus shooting) experimental research design. Results: We demonstrated that individuals who were familiar with physical tasks evaluated predicted and real physical experiences in absolute terms. In addition, we showed that relativistic modes of evaluation applied to real physical experiences but not predicted physical experiences. Conclusions: This research contributes to the debate concerning whether prior task experience influences formation of relative evaluations, and reveals that contexts that urge for relative evaluations undermine happiness with physical tasks.